Radical islam – infectious fear and cultural immunological reactions - Zydorowicz, Jacek (Człowiek i Społeczeństwo, 2016)
Globalization is often treated as a catch-all category, which is a universal frame of reference in the discourse of the humanities, social studies, but also economic, political, and many other fields. Depending on the perspective, some evaluate it very positively, recognizing the benefits; others, on the contrary, point out the threats, and undesirable side effects. Meanwhile, in the reflection on religions, globalization launches a range of fears and concerns (more or less openly articulated). The unquestionable ally of this phenomenon is the modern media, whose tabloid nature is more emotional than rational. Religious conflicts are often overexposed, which, in turn, accelerates tension and social phobias. Both the mainstream media and the propaganda of the Islamic State are trying to imitate the rhetoric known from the movies at the cinema. As a result, by such pop-culture cliches the Western world interprets the influx of Syrian refugees as a cultural invasion (or a religious crusade). This creates a situation of a widespread infection of fear, which triggers the cultural immune responses: rationalizations, denial, conspiracy theories, humour and aggression. Visual artists propose quite a different repertoire of resistance tactics.